The Influence of Knowledge Management and Organizational Learning through Organizational Commitment on Organizational Performance - Tiara Fitriana Azizah; Novita Sari; Silviana Fitri; Edy Hartono (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study aims to analyze the Mediating Role of Organizational Commitment in the influence of Knowledge Management and Organizational Learning on Organizational Performance at Perum Perhutani Regional Division of West Java and Banten. By using a quantitative approach and collecting data from 161 respondents through a questionnaire survey, the results showed that the three variables have a significant influence on employee performance. This finding confirms the importance of these factors in improving overall organizational performance. Although this study has limitations in terms of limited sample size and data collection methods that may lead to bias, the implications of this study provide valuable insights for the development of organizational strategies in the public sector. It is recommended that future research expand the sample size, involve more regional divisions, and consider other factors that could potentially affect organizational performance. Longitudinal research may also provide a deeper understanding of the relationship between the variables studied.